Pengembangan Model Perencanaan Jenjang Karier Berbasis Kompetensi: Studi Kasus Rumah Sakit Pendidikan Unhas, Indonesia - Alam, Nur; Arifah, Nur; Yulistina, Imung; Hadianto, Farmady; Kalsum, Ummu; AS, Andi Indahwaty (LPPM Universitas Respati Indonesia, 2025)
This research aims to analyze the core competencies, role competencies and functional competencies of each position and design a career path as a competency-based simulation at the Unhas teaching hospital. This research uses a case study with an exploratory design, while this type of research is descriptive qualitative with data sources for 117 positions in the Unhas Teaching Hospital. While the data collection techniques used are through questionnaires and documentation. Data analysis techniques used descriptive analysis to obtain core competencies, role competencies and functional positions and cluster analysis using SPSS which aims to obtain groups of positions based on the closeness / similarity of competencies between one position and another. The results of cluster analysis show that the group formed consists of 7 clusters, where positions within the clump of positions can be rotated and promoted directly. Thus, it can be done to determine the standard competency needs of positions and design competency-based position career paths at the Unhas Teaching Hospital.